Long-term shifts in the colony size structure of coral populations along the Great Barrier Reef. Issue 1936 (14th October 2020) - Dietzel, Andreas; Bode, Michael; Connolly, Sean R.; Hughes, Terry P.
Abstract : The age or size structure of a population has a marked influence on its demography and reproductive capacity. While declines in coral cover are well documented, concomitant shifts in the size-frequency distribution of coral colonies are rarely measured at large spatial scales. Here, we document major shifts in the colony size structure of coral populations along the 2300 km length of the Great Barrier Reef relative to historical baselines (1995/1996). Coral colony abundances on reef crests and slopes have declined sharply across all colony size classes and in all coral taxa compared to historical baselines. Declines were particularly pronounced in the northern and central regions of the Great Barrier Reef, following mass coral bleaching in 2016 and 2017. The relative abundances of large colonies remained relatively stable, but this apparent stability masks steep declines in absolute abundance. The potential for recovery of older fecund corals is uncertain given the increasing frequency and intensity of disturbance events. The systematic decline in smaller colonies across regions, habitats and taxa, suggests that a decline in recruitment has further eroded the recovery potential and resilience of coral populations.